Tikal, Copán : Travel Guide : A Complete Guide to All of the Maya Ruins of Central America - Hellmuth, Nicholas M. (Foundation for Latin American Anthropological Research)
Guía turística centrada en la valor patrimonial e histórico de las zonas mayas de Tikal y Copán.